Managing cognitive load in simulations: exploring the role of simulation technologists - Sibbald, Matt; Wang, Bingxian; Caners, Kyla (Canadian Medical Education Journal, 2019)
Background: Facilitating simulation is a complex task with high cognitive load. Simulation technologists are often recruited to help run scenarios and lower some of the extraneous load. We used cognitive load theory to explore the impact of technologists on instructors, identifying sources of instructor cognitive load with and without technologists present. Methods: Data was collected from 56 simulation sessions for postgraduate emergency medicine residents. Instructors delivered 14 of the sessions without a technologist. After each session, the instructor and simulation technologist (if present) provided quantitative and qualitative data on the cognitive load of the simulation. Results: Instructors rated their cognitive load similarly regardless of whether simulation technologists were present. However, the composition of their cognitive load differed. Instructors experienced less cognitive load related to the simulator and technical resources when technologists were present. Qualitative feedback from instructors suggested real consequences to these differences in cognitive load in (1) perceived complexities in running the scenario, and (2) observations of learners. Conclusions: We provide evidence that simulation technologists can remove some of the extraneous load related to the simulator and technical resources for the instructor, allowing the instructor to focus more on observing the learner(s) and tailoring the scenario to their actions.